Výkonnost podniku v podmínkách udržitelného rozvoje - Kožená, Marcela (Univerzita Pardubice, 2008)
The concept of sustainable development includes the economic, environmental and social dimension. Its application to the corporate sector burdens the economic entities with the using of environmental technologies and saving non-renewable resources. The greening of business processes may, under certain conditions, increases the efficiency of the company and strengthen its market position. The paper is specialized on the using of Balanced Scorecard to evaluation of the efficiency of the company in conditions of sustainable development.
Keywords: Sustainable Development; efficiency of enterprise; Balanced ScoreCard; perspectives